2021
DOI: 10.30773/pi.2021.0019
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Work-Related Stress May Affect Depressive Symptoms in Nursing Professionals during the COVID-19 Pandemic Era

Abstract: Objective We aimed to investigate the effect of nursing professionals’ resilience on their mental health, work-related stress, and anxiety in response to the COVID-19 pandemic.Methods We conducted an online survey in the Asan Medical Center and Ulsan University Hospital, South Korea. We extracted data of 824 nursing professionals who consented to participate, including demographic variables and the Stress and Anxiety to Viral Epidemics-9 (SAVE-9), PHQ-9, GAD-7, and Brief Resilience Scale scores.Results Resilie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 39 publications
3
33
1
5
Order By: Relevance
“…Through resilience, emotion-focused strategies were negatively related to psychological distress directly and indirectly in a sample of Spanish nurses [ 42 ]. Resilience was negatively correlated with depression, stress and anxiety [ 44 , 46 , 54 , 65 , 68 , 71 ]. Age, work experience and level of education had a significant positive correlation with nurses’ resilience score [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through resilience, emotion-focused strategies were negatively related to psychological distress directly and indirectly in a sample of Spanish nurses [ 42 ]. Resilience was negatively correlated with depression, stress and anxiety [ 44 , 46 , 54 , 65 , 68 , 71 ]. Age, work experience and level of education had a significant positive correlation with nurses’ resilience score [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…As evidenced by previous research, psychological resilience is a fundamental variable in reducing and preventing the negative psychological effects of the pandemic [ 18 ]. In our review, we found that resilience is associated with lower levels of depression, anxiety and burnout [ 44 , 46 , 53 , 54 , 65 , 68 , 71 ]. Resilience improves personal growth and perceived professional benefits [ 33 , 53 ] and has a positive impact on work engagement even in non-healthcare workers [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, resilience mediated the influence of viral anxiety on psychological well-being among all participants. In COVID-19 pandemic, people's high level of resilience was reported to related with low level of stress and high level of psychological well-being among the general population ( 54 ), even in special population such as public workers ( 55 ), schoolteachers ( 56 ), or healthcare workers ( 57 ). In this sample, however, we could not observe mediating effect of resilience among participants who were more stressful to Beirut explosion.…”
Section: Discussionmentioning
confidence: 99%
“…The SAVE-work stress factor, in contrast, was somewhat less restricted to work-related issues. To our knowledge, the SAVE-9 scale has been used in three further publications [29][30][31], but these did not focus on the psychometrics of the scale.…”
Section: Mental Health Of German Hcw During the Pandemicmentioning
confidence: 99%